An Analysis of Push and Pull Motivation Factors Among Women Entrepreneurs - Syhabuddin Al Tapsi; Athaur Rahman (Saree: Research in Gender Studies, 2025)
Entrepreneurship has been recognized as a driving activity for innovation and economic growth. There is great potential to improve global economic conditions through a better understanding of the increased empowerment of women in entrepreneurial activity. In order to increase women's entrepreneurial activity, it is important to increase knowledge about what motivates women to start a business, which will raise awareness and provide information on how best to support women entrepreneurs. We identified women's motivations for entrepreneurship using push-pull theory. The analytical approach used in this study through a systematic literature review. Based on previous studies, we listed the push-pull factors that motivate women entrepreneurs to pursue entrepreneurial activities. Furthermore, we found that pull factors such as family, business, and independence play a more important role in motivating women while running their businesses than push factors (e.g., job, family, and dissatisfaction). AbstrakKewirausahaan telah diakui sebagai aktivitas pendorong bagi inovasi dan pertumbuhan ekonomi suatu negara. Terdapat potensi besar untuk memperbaiki kondisi ekonomi global melalui pemahaman yang lebih baik tentang peningkatan pemberdayaan perempuan dalam aktivitas kewirausahaan. Untuk dapat meningkatkan aktivitas perempuan dalam berwirausaha, penting untuk meningkatkan pengetahuan tentang motivasi apa saja yang memicu perempuan untuk membangun usaha, sehingga akan meningkatkan kesadaran dan memberikan informasi mengenai cara terbaik untuk mendukung wirausaha perempuan. Kami mengidentifikasi motivasi perempuan dalam berwirausaha dengan menggunakan teori dorongan-tarikan motivasi. Pendekatan analisis yang digunakan pada penelitian ini melalui systematic literature review. Berdasarkan pada penelitian-penelitian terdahulu, kami membuat daftar faktor dorongan-tarikan yang memotivasi perempuan wirausaha dalam menjalankan aktivitas kewirausahaan. Selanjutnya kami menemukan bahwa, faktor tarikan seperti keluarga, bisnis, dan kemandirian memainkan peranan lebih penting dalam memotivasi perempuan pada saat menjalankan usahanya daripada faktor dorongan (pekerjaan, keluarga, dan ketidakpuasan).